Professional orientation and graduate studies in nursing - Malliarou, Maria; Sarafis, Pavlos (My University, 2009)
The aim of the present study is to investigate criteria used in choosing the nursing profession through programs of professional orientation.
Keywords: Professional οrientation; Νursing profession